Trypanosoma evansi in horses from the Colombia - Associated Infection Factors - Rodríguez Durán, Arlex; Muñoz Duque, Julián David; López Osorio, Sara; Chaparro Gutiérrez, Jenny Jovana; Cortés Vecino, Jesús Alfredo (Acta Scientiae Veterinariae, 2023)
Background: Trypanosoma evansi is the most common protozoan in tropical and subtropical regions of the world, due to its ability to maintain and be transmitted by vectors such as Stomoxys spp. and Tabanus spp. This protozoan causes high morbidity and mortality rates in horses in African, American and Asian countries. In the years 2021 and 2022, a high mortality rate was reported among horses with symptoms associated with Trypanosoma spp. in the municipality of Arauca, department of Arauca, Colombia. The investigation described here was therefore carried out, seeking to identify the pathogens and risk factors that led to the death of the horses in this region of Colombia. Cases: Blood samples were collected from Colombian criollo horses and dogs, as were samples of ticks, flies and horseflies that infested the horses. A variety of tissue samples were removed from the horses a few min after their death for histopathological analysis. Two questionnaires were applied to obtain information about the horses and the environment in which they live. The results of the clinical examination revealed pale mucous membranes, jaundice, high fever, dehydration and lethargy. The horses were also infested with Amblyomma mixtum (17.6%) and Dermacentor nitens (82.4%) ticks, and with Tabanus pungens (74%), Tabanus spp. (26%), and Stomoxys calcitrans flies (100%), while the dogs were infested with Rhipicephalus sanguineus s.l. (77.7%) and Amblyomma mixtum (22.2%) ticks. The blood smear test results revealed the presence of Trypanosoma spp. in 66.6% (n = 4) of the horse blood samples, and in 50% (n = 1) of the dog blood samples. PCR performed to identify the Trypanosoma species confirmed the presence of T. evansi. Histological examination of the spleen revealed the involvement and dissemination of T. evansi in the tissues. The horses also showed the presence of Equine Infectious Anemia Virus (EIAV). Discussion: This is the first updated specific report of T. evansi in criollo horses in the savannah flood zone of the municipality of Arauca, Colombia. The main risk associated with T. evansi infection in horses was found to be infestation with the natural vector T. pungens and the mechanical vector S. calcitrans, which are efficient ectoparasites for the transmission of this parasite. The presence of T. evansi in dogs represents a constant risk to horses, because dogs may serve as a reservoir for the maintenance of the hemoparasite in the population under study. Another risk factor for horses could be the presence of vampire bats (Desmodus rotundus), a species of bat that has been described as a vector and reservoir of T. evansi in Colombia. The presence of EIAV antibodies in the horses under study can be attributed to the exposure of sick horses to vectors of this virus, such as Tabanus spp., S. calcitrans and inanimate needle-shaped fomites. This is the first study that identifies the coinfection of T. evansi and EIAV in horses in the floodplain region of Colombia. In view of the importance of these 2 pathologies to the health of horses, a greater number of tests and a larger animal population will be required to determine if this coinfection is the cause of the death of criollo horses in this region of Colombia. Lastly, the owners reported that pharmacological control with trypanocides has not been successful in most of the outbreaks that occurred during the years 2021 and 2022. This may suggest that Trypanosoma evansi is developing resistance to these drugs; therefore, specific studies will be required in the future to test this hypothesis. Keywords: Arauca, Equine Infectious Anemia Virus, floodplain savannah, mortality, surra.